2009
DOI: 10.1007/s10533-009-9284-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil amino-acid availability across a temperate-forest fertility gradient

Abstract: Despite increasing recognition that free amino acids can be an important source of N for plant uptake, we have a poor understanding of environmental variation in the availability of amino-acid N in soils outside of arctic, alpine and boreal regions. I investigated patterns of amino-acid availability along a temperate forest fertility gradient ranging from low mineral N availability, oak-dominated forests to high mineral N availability, maple-basswood forests (5 sites). I measured standing pools of free amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…Cellular catabolism of amino acids allows these nitrogen resources to be further distributed into other compounds. In this way, the microbes may better adapt to amino acid resources that display compositional heterogeneity, and are variably available spatially and temporally (Rothstein, 2009). It has been hypothesized that ammonia originating from catabolism of amino acids may be one source of nitrogen transferred from ECM fungi to their symbiotic plant hosts (Chalot et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular catabolism of amino acids allows these nitrogen resources to be further distributed into other compounds. In this way, the microbes may better adapt to amino acid resources that display compositional heterogeneity, and are variably available spatially and temporally (Rothstein, 2009). It has been hypothesized that ammonia originating from catabolism of amino acids may be one source of nitrogen transferred from ECM fungi to their symbiotic plant hosts (Chalot et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing evidence that amino acid pools are relatively more abundant in temperate forests where N mineralization rates are low (Finzi and Berthrong 2005;Gallet-Budynek et al 2009;Rothstein 2009), providing a pool of potentially plant-available N in what were previously considered low-fertility habitats. Also, a few studies have shown that temperate trees have the ability to use amino acid N (Bennett and Prescott 2004;Hofmockel et al 2007;Warren and Adams 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, soluble N pools in the soil contain a wide variety of different amino acids with varying abundances and molecular structures (Kielland 1995;Yu et al 2002;Rothstein 2009). While glycine is often one of the dominant free amino acids in field soil solutions, ranging from approximately 5 to 20% of total free amino acids depending on the ecosystem (Kielland 1995;Rothstein 2009), other amino acids can occur in equal or greater concentrations (Senwo and Tabatabai 1998;Raab et al 1999), suggesting that glycine uptake potential alone does not necessarily represent plant access to amino acid N pools.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations